Change in Slurry/Glass Interfacial Resistance by Chemical Mechanical Polishing. (8th May 2017) - Sugimoto, Taku; Suda, Seiichi; Kawahara, Koichi
ABSTRACT: The use of ceria abrasives in the chemical mechanical polishing (CMP) of glass allows us to prepare extremely smooth surfaces because it aides both the chemical and mechanical aspects of the polishing process. The mechanism of CMP has remained vague, but the redox of Ce 4+ /Ce 3+ would play a major role for the formation of hydration layer by the chemical factors of CMP. This redox accompanies the process of the charge transfer at glass/slurry interface. Electron charge carrier would be important role in chemical polishing if the redox reaction occurs during polishing. We then prepared the polishing model that it is possible to estimate slurry resistivity and the interfacial area specific resistance (ASR). The effects of abrasive compositions and slurry solution on chemical factor of CMP were investigated to clarify CMP mechanism. The hydration layer forms as a result of the shear stress during polishing but is independent of polishing loads. The amount of hydration layer as well as removal rate was increasing with increasing lanthanum concentration dissolved in ceria lattice. Small amount addition of NH4 NO3 increase electron charge carrier density in slurry and improves removal rate, but excess addition inhibited hydration reaction by steric hindrance.